Ferro- kinetic studies in a variety of haematological disorders, acute porphyria and scurvy - Kramer, Sydney (My University, 1960)
Since changes occur in size, shape and haemoglobin content of red cells in disease a classification of the anaemias based on the morphology of the red cell has been widely used ( Wintrobe, 1956 ) . While such classification has a limited usefulness from the diagnostic and therapeutic approach it has two serious defects..
A thesis presented to the Faculty of Medicine, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Medicine
Keywords: Kinetics; Hematologic Diseases; Porphyria, Acute Intermittent; Scurvy